Advances on P2P, parallel, grid, cloud and internet computing : proceedings of the 12th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2017) /: proceedings of the 12th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2017). (2018) - Unknown
No abstract available